Safety and efficacy of a feed additive consisting of Lactiplantibacillus plantarum (formerly Lactobacillus plantarum) IMI 507027 for all animal species (ALL‐TECHNOLOGY (IRELAND) LIMITED [Alltech Ireland]) - EFSA Panel on Additives and Products or Substances used in Animal Feed (FEEDAP); Vasileios Bampidis; Giovanna Azimonti; Maria de Lourdes Bastos; Henrik Christensen; Birgit Dusemund; Mojca Fašmon Durjava; Maryline Kouba; Marta López‐Alonso; Secundino López Puente; Francesca Marcon; Baltasar Mayo; et al. (EFSA Journal, 2021)
Abstract Following a request from the European Commission, the Panel on Additives and Products or Substances used in Animal Feed (FEEDAP) was asked to deliver a scientific opinion on the safety and efficacy of Lactiplantibacillus plantarum (formerly Lactobacillus plantarum) IMI 507027 as a technological additive for all animal species. The additive is intended to improve the production of silage at a proposed application rate of 1 × 109 colony forming units (CFU)/kg fresh material. The bacterial species L. plantarum is considered by EFSA to be suitable for the qualified presumption of safety approach. As the identity of the strain has been established and no antimicrobial resistance determinants of concern were detected, the use of the strain as a silage additive is considered safe for livestock species, for consumers and for the environment. In the absence of data, the FEEDAP Panel cannot conclude on the potential of the additive to be a skin/eye irritant or a skin sensitiser. Given the proteinaceous nature of the active agent, the additive should be considered a respiratory sensitiser. The additive at the proposed application rate of 1 × 109 CFU/kg fresh material has the potential to improve the fermentation of the silages from easy to moderately difficult to ensile forages.